Sosialisasi Proses Pengolahan Limbah Cair Di Dhillon Medical Centre Deli Serdang - Huwaina Af’idah; Nisrina Nisrina; Abdul Karim (Akademi Analis Kesehatan Pekalongan, 2023)
Background: Pharmaceutical and hospital industrial wastewater is a potential source of environmental pollution. Therefore, the waste water needs to be treated first before being discharged into public channels. The problem that often arises in terms of hospital waste management is the limited funds available to build waste processing facilities and operational costs, especially for small and medium hospitals. To overcome this, it is necessary to develop wastewater treatment technology that is cheap, easy to operate and affordable, especially for small pharmaceutical industries and hospitals with small to medium capacity. Objective: The aim of this research is to increase understanding for workers, especially in the waste processing section, so that they have the ability and understanding in their daily implementation. Methods: The methodology of this research is use quantitative design with one group pretest and posttest with intervention group design. The questionnaire was used as a pre-test and post-test, by determining the average number of respondents who understood the information before and after being socialized on the waste processing section. Results: The research did in March 2023 in Dhillon Medical Centre Deli Serdang whom 16 participants. The results of service activities show that the knowledge of workers in Dhillon Medical Centre increased by >50% after being given material presentations by the PKM team. Conclusion and Suggest: The suggestion given is to increase cross-sector collaboration between decision makers, so as to reduce the risk of environmental pollution